PENGEMBANGAN BUKU KOMIK BERBASIS SOSIO SCIENTIFIC ISSUES UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Diana Fadilla; Awalina Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The level of student engagement is low and there is an urgent need to improve the quality of student learning at the elementary level. This research aims to improve the critical thinking skills of elementary school students in class V. This research uses Research and Development (R&D) with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, evaluation. Comic book media was declared "Very Valid" for testing as proven by the results of the media validator who obtained a media percentage of 95%, material 100%, and language 100%. Teacher responses and student responses to comic book media obtained a teacher response of 95%, medium scale 95% and large scale 89.3% declared "Very Appropriate" as a science learning media. The N-Gain Score test is used to calculate the increase in critical thinking skills from the results of the pretest and posttest which obtained a significance of 0.59 with the "Medium" criteria. It was concluded that comic books based on socio-scientific issues as science learning media can improve the critical thinking skills of fifth grade elementary school students.